Rolling contact fatigue performance of a TiN coating deposited on AISI 440C by plasma based ion implantion and deposition - Mara Paula Gonzlez; Diego A. Colombo; Diego O. Fernandino (Fracture and Structural Integrity)
In this work, the microstructural evolution, surface characteristics and wear behavior of high hardness AISI 440C samples coated with a TiN film synthesized at room temperature were investigated. The coating was deposited using a combined process of plasma-based ion implantation and deposition (PBII and D). Rolling contact fatigue (RCF) tests were conducted and compared with those of the uncoated steel. Tests were carried out in a flat washer type testing rig under lubricated pure rolling conditions. The results indicate that the microstructure of the substrates remained unchanged after the deposition process. The application of the coatings produced an increase in the arithmetic average height of the roughness profiles and a change in their skewness. The adhesion of the TiN coating on AISI 440 C proved to be satisfactory. RCF test generated typical fatigue spalls in the uncoated samples. In coated samples partial delamination of the coating occurred along the rolling track. Taking partial delamination of the coating as a failure criterion, it was found that the RCF life of the coated samples was higher than that of the uncoated ones.